Bulky Lesion Bypass Requires Dpo4 Binding in Distinct Conformations. - Liyanage,PS; Walker,AR; Brenlla,A; Cisneros,GA; Romano,LJ; Rueda,D (Sci Rep, 2017)
Translesion DNA synthesis is an essential process that helps resume DNA replication at forks stalled near bulky adducts on the DNA. Benzo[a]pyrene (B[a]P) is a polycyclic aromatic hydrocarbon (PAH) that can be metabolically activated to benzo[a]pyrene diol epoxide (BPDE), which then can react with DNA to form carcinogenic DNA adducts. Here, we have used single-molecule florescence resonance energy transfer (smFRET) experiments, classical molecular dynamics simulations, and nucleotide incorporation assays to investigate the mechanism by which the model Y-family polymerase, Dpo4, bypasses a (+)-cis-B[a]P-N 2-dG adduct in DNA. Our data show that when (+)-cis-B[a]P-N 2-dG is the templating base, the B[a]P moiety is in a non-solvent exposed conformation stacked within the DNA helix, where it effectively blocks nucleotide incorporation across the adduct by Dpo4. However, when the media contains a small amount of dimethyl sulfoxide (DMSO), the adduct is able to move to a solvent-exposed conformation, which enables error-prone DNA replication past the adduct. When the primer terminates across from the adduct position, the addition of DMSO leads to the formation of an insertion complex capable of accurate nucleotide incorporation.